Amulet. Book seven, Firelight - Kibuishi, Kazu, 1978- (New York : Graphix, 2016)
Emily, Trellis, and Vigo visit Algos Island, where they can access and enter lost memories. They're hoping to uncover the events of Trellis's mysterious childhood-knowledge they can use against the Elf King. What they discover is a dark secret that changes everything. Meanwhile, the Voice of Emily's Amulet is getting stronger, and threatens to overtake her completely.
2.8
3-6
GN410L
S
Keywords: Single-parent families -- Fiction; Magic -- Fiction; Single-parent families -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Memory -- Fiction; Amulets -- Fiction; Fantasy; Graphic novels; Fantasy comics; Graphic novels; Graphic novels; Comics (Graphic works)